Discurso publicitário da sustentabilidade: um estudo das estratégias persuasivas em anúncios de revista - Verissimo, Fabiane da Silva (2013)
This study search for analysing how persuasive strategies used in publicity propose cultural values in societies in order to assure the notion of sustentability. To do so reflects advertisement is treated as a persuasive, strategical phenomenon able to spread ideas and convictions regarding values. Next, perspectives and basis about sustentability are shown related to social practices in environment and yet to get this it is necessary a brief reflection on the logic of consumption and its effects on contemporary society. SubSeguently the methodology is based on the theoreticmethodological proposal of social speeches in order to understand the sense effects produced by ads in magazines. So, the analysis tries to understand how the subjects are related to the speech, as well as the theme investments in which the advertiser organizes his logic of persuasion to affirm values about sustentability. To get this it will be search: the effects from the advertisement, what it tells us, the reality and the theme in advertisements found in national magazines.